Generic instruments for drug discontinuation in primary care: A systematic review. Issue 7 (5th April 2020) - Michiels‐Corsten, Matthias; Gerlach, Navina; Schleef, Tanja; Junius‐Walker, Ulrike; Donner‐Banzhoff, Norbert; Viniol, Annika
Abstract : Aims: The aim of this systematic review was to identify generic instruments for drug discontinuation in patients with polypharmacy in the primary care setting. Methods: We systematically searched PubMed and EMBASE, 8 guideline databases (AWMF, NICE, NGC, SIGN, NHMRC, CPG, KCE), the Cochrane Library and grey literature (Google) in 2016 and 2017. Two independent researchers screened and analysed data. The drug discontinuation instruments of the included publications were described and classified. Results: We identified 16 relevant publications. Here we found complex algorithms as well as instruments composed of distinct sequential steps. Two guidelines are constructed as electronic web‐applications. Instruments revealed diverging emphases on the stages of deprescribing, i.e. preparation, drug evaluation, decision‐making and implementation. Accordingly, 3 types of instruments emerged: general frameworks, detailed drug assessment tools and comprehensive discontinuation guidelines. Conclusion: Diverse generic instruments exist for different areas of applications in regard to drug discontinuation. However, there is still a need for practical and user‐friendly tools that support physicians in communicational aspects, visualise trade‐offs and also enhance patient involvement.